The effects of the insulin resistance index on the virologic response to entecavir in patients with HBeAg-positive chronic hepatitis B and nonalcoholic fatty liver disease - Zhu LY; Wang YG; Wei LQ; Zhou J; Dai WJ; Zhang XY (Dove Medical Press, 2016)
Li-Yao Zhu,1,* Yu-Gang Wang,2,* Li-Qing Wei,3,* Jian Zhou,1 Wei-Jie Dai,4 Xiao-Yu Zhang5,6 1Department of Hepatology, The Fourth People’s Hospital of Huai’an, Huai’an, Jiangsu, 2Department of Gastroenterology, Shanghai Tongren Hospital, Shanghai Jiao Tong University School of Medicine, Shanghai, 3Department of Medical Laboratory, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 4Department of Gastroenterology, Huai’an First People’s Hospital, Nanjing Medical University, 5Division of Gastrointestinal Surgery, Department of General Surgery, The Affiliated Huai’an Hospital of Xuzhou Medical College, 6Division of Gastrointestinal Surgery, Department of General Surgery, The Second People’s Hospital of Huai’an, Huai’an, Jiangsu, People’s Republic of China *These authors contributed equally to this work Purpose: To further observe and verify the effect of nonalcoholic fatty liver disease (NAFLD) on the response to antiviral therapy in patients with chronic hepatitis B (CHB) and investigate the relationship between the virologic response and insulin resistance. Patients and methods: A retrospective study was adopted and 61 NAFLD patients with HBeAg-positive CHB were included as the observation group (group A), and 64 patients with simple CHB were included as the control group (group B). Results: After 12 weeks of treatment with entecavir, the total virologic response rate in group A was statistically significantly lower than that in group B (P<0.05). During weeks 24–96, the difference was not statistically significant (P>0.05). In weeks 48 and 96, there was no significant difference in the HBeAg seroconversion rates between the two groups (P>0.05). In weeks 12 and 24, there was also no significant difference in the alanine transaminase (ALT) normalization rate between the two groups (P>0.05). Then, in weeks 48 and 96, the ALT normalization rate of group A was obviously lower than that of group B (P<0.05). Group A patients were divided into group A1 (≤M) and group A2 (>M) according to the median value (M=2.79) of the baseline homeostatic model assessment method insulin resistance levels. In weeks 48 and 96, the ALT normalization rate of group A1 was significantly higher than that of group A2 (P<0.05). The correlation coefficient (r) of the baseline homeostatic model assessment method insulin resistance level and the severity of fatty liver in group A was 0.426 (P=0.001). Conclusion: NAFLD cannot affect the long-term total virologic response rate and HBeAg seroconversion rate in CHB patients treated with entecavir but can reduce the long-term biochemical response rate, which has a positive correlation with the severity of fatty liver and the insulin resistance index. Keywords: hepatitis B virus, chronic, fatty liver, entecavir, insulin resistance index